2022
DOI: 10.17219/dmp/145759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of botulinum toxin in patients with myofascial pain related to temporomandibular joint disorders: A systematic review

Abstract: Botulinum toxin is used as an alternative for the treatment of chronic refractory myofascial pain derived from temporomandibular disorders (TMDs). It is important to establish the benefits of botulinum toxin in this type of symptomatology. The aim of the study was to conduct a systematic review in order to evaluate the effects of botulinum toxin in patients with myofascial pain related to temporomandibular disorders. The search was carried out systematically, without limitations of language or year of publicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Biofeedback was performed by placing surface electrodes on the skin to measure the frequency, intensity and duration of muscle contractions in order to decrease the tension of cramped muscles or increase the activity of weak muscles [ 17 ]. Meanwhile, botulinum toxin mainly inhibited the release of inflammatory transmitters from sensory nerve endings, while it could achieve flaccidity by inhibiting the release of acetylcholine from nerve endings [ 18 ]. Platelet rich plasma (PRP) was obtained by centrifugation of autologous blood.…”
Section: Discussionmentioning
confidence: 99%
“…Biofeedback was performed by placing surface electrodes on the skin to measure the frequency, intensity and duration of muscle contractions in order to decrease the tension of cramped muscles or increase the activity of weak muscles [ 17 ]. Meanwhile, botulinum toxin mainly inhibited the release of inflammatory transmitters from sensory nerve endings, while it could achieve flaccidity by inhibiting the release of acetylcholine from nerve endings [ 18 ]. Platelet rich plasma (PRP) was obtained by centrifugation of autologous blood.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a few systematic reviews assessed the use of BTX-A therapy for myofascial pain. 5,7,31 One systematic review without meta-analysis reported a reduction in pain intensity in BTX-A groups in three studies, while one study showed no difference in pain compared with placebo. 7 Another review reported that BTX-A was effective in treating refractory myofascial pain.…”
Section: Discussionmentioning
confidence: 99%
“…7 Another review reported that BTX-A was effective in treating refractory myofascial pain. 31 One meta-analysis of four clinical trials on BTX-A versus placebo found that BTX-A was slightly more effective than placebo for pain reduction at 1 month, but showed no difference at 3 and 6 months. 5 Our results align with previous reviews, indicating that BTX-A is effective in improving pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 30 years, accumulated evidence has established the effectiveness of BoNT-A [ 11 , 15 , 16 , 17 ]. BoNT-A plays also a role in the management of other conditions, such as chronic migraine, focal dystonia, hemifacial spasm, myofascial pain, and cerebral palsy [ 18 , 19 , 20 , 21 ]. Despite the considerable and well-known beneficial effects, many patients suffering from spasticity discontinue treatment.…”
Section: Introductionmentioning
confidence: 99%